ANALISIS YURIDIS PROSES HUKUM TERHADAP PEJABAT DIPLOMATIK YANG MELAKUKAN PERBUATAN MELAWAN HUKUM DI NEGARA PENERIMA (STUDI KASUS ASUSILA PEJABAT DIPLOMAT MALAYSIA DI WELLINGTON, SELANDIA BARU) - Oktaviana, Ruth; Bachtiar, Maryati; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Immunity of diplomatic officials is freedom from arrest or detention. This freedom is a guarantee for one diplomatic official in conducting its functions. Each emphasis directly against a diplomat who represented his country could be considered as aimed directly against the countries they represent, but a diplomat are also obliged to respect the rules and laws of the recipient country.This study aims to determine the provisions of Vienna Convention of 1961 that regulates the immunity and privileges of diplomatic officials and legal processes that must be followed by a diplomatic official who committed an unlawful act in the recipient country.This research is a form of literature studies, which are guided by the development of science of international law, especially in the diplomatic field. From this research can be seen the advantages of immunity and inviolability, which is given to diplomatic officials, associated with the execution of their functions and duties. However, from the advantages it can be seen the individuals who misuse these immunity.Results from this study would be refers to the case between New Zealand and Malaysia with the provisions on the rights of immunity and the privileges of an officials diplomatic for contained in the 1961 Vienna Convention.The provisions about the waiver of immunity and the rule of law are stated in Section 32 of the Vienna Convention 1961. Immunity of jurisdiction of diplomatic officials and those who enjoy the immunity contained in Section 37 of the Vienna Convention 1961 can be removed by the sending country. Dismantlement of immunity the diplomat who violate depends on the good faith of the sending country in ensuring that the diplomat will get fair treatment in the country. Because in Vienna Convention 1961 on Diplomatic Relations does not explain about the standard or a reason to be abandon immunity of a diplomat who commit violations.Thus, the authors suggest for more coordination between the government and the police related to the arrest and detention of diplomatic officials who proved to have committed acts of crime in the territory of New Zealand, so that all processes that run against diplomatic officials can be run in accordance with the rules of international law applicable in New Zealand.Keywords: Immunities and Privileges of Diplomatic Officials, Legal Process of Diplomatic officials, associated with cases immoral.